3d Printing: Basic principles and applications. (2022) - Thakar, Chetan M.; Parkhe, Shailesh S.; Jain, Ankit; Phasinam, Khongdet; Murugesan, G.; Ventayen, Randy Joy Magno
Abstract: Due to the economic growth and worldwide interference with today's globalization and industrialization, the manufacturing sector has gained greater prominence in the last decade. Many fresh revolutionary tactics have been created, and revolution is an endless narrative. Recent popularity for 3D and additive printing concerns established norms worldwide. In contrast, the manufacture rate, quality and efficiency of existing systems are greatly enhanced. This recurrent technological transformation pushes firms to adopt these new technologies to their production methods. Most manufacturers are unlikely to fit into the new system because of a number of issues such as capital shortages, lack of funds, lack of knowledge, lack of professional organizations and so on. Besides with these technical advances may also play a major part in influencing the industrial industry, both ethical and reputational. In addition to consideration of supply chain risks and resilience, the recent growth in the manufacturing industry focusing on sustainability changes the way manufacturers are thinking. Multi-perspective analyzes are necessary for surviving to endure in the production environment. Contrary to this, manufacturers and shareholders have been showing in the last several years that the financial benefits not only improve production but also bring considerable returns to the business in view of the ecological and social advantages. In recent years, manufacturers have had a huge push in combination with economic, environmental and social principles to look at technical advancement.